Evaluation of the Territorial Distribution of Health Care Financing - Žemgulienė, Jolanta (Ekonomika, 1999)
The article investigates morbidity as one possible criteria of the rationality of the health care financing territorial distribution. Regional morbidity and financing differences have been analysed according to that criteria, correlation coefficient of the linear relationship between territorial data on morbidity and financing have been defined. The results showed that one criteria is not sufficient proof to determine the rationality of territorial distribution of financing. Although there is no linear correlation between morbidity and financing, the differences of territorial morbidity and financing are not statistically significant. There were found statistically significant urban and rural differences between the financing per 1 inhabitant of the institutions within the regional jurisdiction.